1999
DOI: 10.1074/jbc.274.10.6770
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Stimulates Lipolysis in Adipocytes by Decreasing Gi Protein Concentrations

Abstract: Prolonged treatment (12-24 h) of adipocytes with tumor necrosis factor ␣ (TNF␣) stimulates lipolysis. We have investigated the hypothesis that TNF␣ stimulates lipolysis by blocking the action of endogenous adenosine. Adipocytes were incubated for 48 h with TNF␣, and lipolysis was measured in the absence or presence of adenosine deaminase. Without adenosine deaminase, the rate of glycerol release was 2-3-fold higher in the TNF␣-treated cells, but with adenosine deaminase lipolysis increased in the controls to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
2
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 43 publications
5
83
2
4
Order By: Relevance
“…Furthermore, in vitro studies in both rodents and humans have demonstrated that TNF-a stimulates adipocyte lipolysis (Green et al 1994, Ryden et al 2002. In adipocyte cell culture, TNF-a stimulation of lipolysis is only observed after 6-12 h and is therefore dependent on altered gene transcription and/or protein expression (Gasic, et al 1999). TNF-a activation has been shown to lead to downregulation of perilipin (Ryden et al 2002, Zhang et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies in both rodents and humans have demonstrated that TNF-a stimulates adipocyte lipolysis (Green et al 1994, Ryden et al 2002. In adipocyte cell culture, TNF-a stimulation of lipolysis is only observed after 6-12 h and is therefore dependent on altered gene transcription and/or protein expression (Gasic, et al 1999). TNF-a activation has been shown to lead to downregulation of perilipin (Ryden et al 2002, Zhang et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that part of the TNF-␣ effect could be mediated by down-regulation of membrane G␣ i , resulting in abrogated antilipolytic signals (36). Others have suggested that TNF-␣ down-regulates the expression of perilipins, which are small phosphoproteins expressed at the surface of the intracellular lipid droplet (37).…”
Section: Discussionmentioning
confidence: 99%
“…108 Either in relation to HIV-1 infection itself or to HAART, the increase in TNFa and other cytokines in adipose tissue may play a major role in the sustained increase in lipolysis. TNFa, like other cytokines such as interleukin-6, 109 activates lipolysis in adipocytes 110 and has been directly implicated in the increased release of fatty acids from adipose tissue in HALS patients. 111 Moreover, co-culture of adipocytes and macrophages indicates that FFAs released by adipose cells activate TNFa release by macrophages, thus indicating a positive cross-talk between adipocytes and macrophages involving mainly FFA and TNFa release, respectively.…”
Section: The Paradox Of the Common Inflammation Status In Adipose Tismentioning
confidence: 99%